Route Predictions In Mobile Phone Data Using Data Mining Concepts - KRISHNA KUMAR G (2009)
INTERNAL GUIDE : Sreedevi . EXTERNAL GUIDE : Saravana Ranjan USN No : 1MJ06SCS08 CARRIED OUT AT : Intersoftkk (P) Kormangala Bangalore-560 034 ACC NO : PC101
Keywords: M.Tech Computer Science